Hydrodynamic drag of some small sprint kayaks - Lazauskas, L.; Winters, J. (1997)
Some popular small (0.098 m3 displacement volume) sprint kayaks are compared on the basis of their upright, calm-water, total (wave plus viscous) resistance. Comparisons are also made with the drag of some simple mathematical hullforms, and with a kayak optimised for minimum total resistance under constraints intended to give adequate intact stability.